2000
DOI: 10.1080/003655200750056592
|View full text |Cite
|
Sign up to set email alerts
|

Children with Untreated Food Allergy Express a Relative Increment in the Density of Duodenal ?d+ T Cells

Abstract: According to this preliminary observation, high densities of intraepithelial gammadelta+ T cells and a significantly elevated gammadelta+/CD3+ ratio are associated with untreated FA. If seen LNH in a gastroduodenoscopy and/or increased densities of gammadelta+ T cells in the biopsy specimen, the possibility of gastrointestinal FA should be reliably assessed by a food challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 15 publications
6
24
0
Order By: Relevance
“…A patchy enteropathy was found in 60% of patients with cows’ milk allergy, in all cases characterized by duodenal lymphocytosis [56]. A striking increase in γ/δ-positive T-cells has been reported in such patients [57,58]. Further diagnostic clues are increased eosinophils and the association with clinical manifestations of an allergic phenotype.…”
Section: Origin Of Mementioning
confidence: 99%
“…A patchy enteropathy was found in 60% of patients with cows’ milk allergy, in all cases characterized by duodenal lymphocytosis [56]. A striking increase in γ/δ-positive T-cells has been reported in such patients [57,58]. Further diagnostic clues are increased eosinophils and the association with clinical manifestations of an allergic phenotype.…”
Section: Origin Of Mementioning
confidence: 99%
“…It was first described as an age-related finding in children of minimal significance, but further work noted a close association between LNH and the development of food allergies. It was shown that children with LNH were two to three times more likely to have non-IgE mediated allergies to food such as milk or cereal (Kokkonen et al, 1999) including high levels of IgG and IgA against milk proteins (Kokkonen et al, 2002), increased numbers of γδ T cells associated with the lymphoid follicles (Kokkonen et al, 2000), and increased CD4+ T cells with decreased T h1 cytokines (Bellanti et al, 2003). LNH was not found to be associated with Crohn’s disease or NOD2/CARD15 mutations raising speculation that LNH is not related to inflammatory disease, but may be a response to the microbial environment (Shaoul et al, 2006) as children with LNH showed a significant increase in number of bacteria adherent to the intestinal mucosa layer (Conte et al, 2006).…”
Section: Ilf Hyperplasia As a Sign Of Immune Dysfunctionmentioning
confidence: 99%
“…The γδ IEL increase is not totally specific to CD, since it has occasionally been found in other conditions such as cow’s milk intolerance, food allergy, cryptosporidiosis, giardiasis, Sjögren syndrome, and IgA deficiency [11]. However, the increase in γδ IEL in a minority of patients with these conditions tends to be mild and transient [16]. It has been stated that CD is the only disease in which γδ IEL are increased systematically, permanently, and intensely [11], [17][19].…”
Section: Introductionmentioning
confidence: 99%